Cancer patient and provider responses to companion scales assessing experiences with LGBTQI-affirming healthcare - Pratt-Chapman, Mandi L.; Wang, Yan; Quinn, Gwendolyn P.; Shirima, Sylvia; Adler, Sarah; Brazinskaite, Ruta; Kamen, Charles; Radix, Asa; Warren, Barbara; Eckstrand, Kristen; Lopez, Ana Maria (Frontiers in Oncology, 2023)
Background: Sexual and gender minority (SGM) persons are at a higher risk for some cancers and may have poorer health outcomes as a result of ongoing minority stress and cisnormative, heteronormative healthcare environments. This study compared patient and provider experiences of affirming environmental and behavioral cues and also examined provider-reported knowledge, attitudes, behaviors, and clinical preparedness in caring for SGM patients among a convenience sample. Methods: National convenience samples of oncology providers (n=107) and patients (n=88) were recruited separately via snowball sampling. No incentives were provided. After reverse coding of appropriate items for unidirectional analysis, lower scores on items indicated greater knowledge, more affirming attitudes or behaviors, and greater confidence in clinical preparedness to care for SGM patients. Pearson Chi-Square tests compared dichotomous variables and independent samples t-tests compared continuous variables. Results: Both samples were predominantly female sex assigned at birth, cisgender, and heterosexual. Providers were more likely than patients to report affirming cues in clinic, as well as the ability for patients to document their name in use and pronouns. Providers were more likely to report asking about patient values and preferences of care versus patients’ recollection. Patients were more likely to report understanding why they were asked about both sex assigned at birth and gender identity compared to providers’ perceptions that patients would understand being asked about both. Patients were also more likely to report comfort with providers asking about sex assigned at birth and gender identity compared to providers’ perceptions of patient comfort. SGM providers had greater knowledge of SGM patient social determinants of health and cancer risks; felt more prepared to care for gay patients; were more likely to endorse the importance of knowing patient sexual orientation and gender identity; and were more likely to indicate a responsibility to learn about SGM patient needs and champion positive system changes for SGM patients compared to heterosexual/cisgender peers. Overall, providers wished for more SGM-specific training. Conclusion: Differences between patient and provider reports of affirming environments as well as differences between SGM and heterosexual/cisgender provider care supports the need for expanded professional training specific to SGM cancer care.